2016
DOI: 10.1186/s13104-016-2161-9
|View full text |Cite
|
Sign up to set email alerts
|

RNA expression of TLR10 in normal equine tissues

Abstract: BackgroundToll like receptors are one of the major innate immune system pathogen recognition systems. There is little data on the expression of the TLR10 member of this family in the horse.ResultsThis paper describes the genetic structure of the Equine TLR10 gene and its RNA expression in a range of horse tissues. It describes the phylogenetic analysis of the Equine TLR1,6,10,2 annotations in the horse genome, firmly identifying them in their corresponding gene clades compared to other species and firmly placi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…According to the UniProt database, there is evidence of gene transcription for horse TLRs 2–4 and 7–10 , and evidence for translation for TLR9 in domestic horses and donkeys. However, the expression of equine TLR1-10 has been confirmed as well (Astakhova et al 2009 ; Uddin et al 2016 ; Tarlinton et al 2016 ). Dugovich et al ( 2019 ), and Smith et al ( 2020 ) confirmed the expression of TLR2, 5 and 9 in Equus quagga spp .…”
Section: Resultsmentioning
confidence: 93%
“…According to the UniProt database, there is evidence of gene transcription for horse TLRs 2–4 and 7–10 , and evidence for translation for TLR9 in domestic horses and donkeys. However, the expression of equine TLR1-10 has been confirmed as well (Astakhova et al 2009 ; Uddin et al 2016 ; Tarlinton et al 2016 ). Dugovich et al ( 2019 ), and Smith et al ( 2020 ) confirmed the expression of TLR2, 5 and 9 in Equus quagga spp .…”
Section: Resultsmentioning
confidence: 93%
“…Given the similar expression profile, epigenetic regulation of TLR3 could be involved in young foals. The function of TLR10 is not known, although it is expressed in lymphoid cells and tissues of the horse [ 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although this receptor can homodimerize and form heterodimers with TLR1, TLR2, and TLR6 [ 181 , 182 , 183 , 184 ], the functional significance of the resulting complexes and TLR10 itself remains mostly unknown [ 182 ]. It was shown that the TLR10/TLR2 heterodimer and TLR10/TLR10 can bind MyD88, but they are incapable of NF-κB activation [ 185 ]. It seems that TLR10 serves as an inhibitor of the MyD88 dependent and independent pathways [ 86 , 178 ].…”
Section: Structure and Intrinsic Disorder In Tlrs And Major Players I...mentioning
confidence: 99%